EKSISTENSI RUANG TERBUKA PADA LINGKUNGAN PERMUKIMAN - Eva Elviana; Diyan Lesmana (Talenta Publisher, 2019)
The housing environment that appears in many urban areas today, is available in the form of real estate and in the form of simple housing. The existence of these houses is equipped with supporting infrastructure. One of them is the availability of open space as a public facility, which can be utilized by all residents of housing. If you look at the historical aspects of past traditional settlements, such as the Tanean Lanjang Madura settlement, the Samin Bojonegoro Community Village, the Sumatra Karo Batak Village, and so on, it is found that there is open space as a public space. Where the function and role of open space are used for joint activities, gathering places and socializing, as well as the center of orientation of several groups of houses, so that the location tends to be in the center. The purpose of this study is to see the existence of open space of traditional settlements (past) and present. As well as analyzing the activities carried out by the pas community and its current development. By using the method of field observation (observation) and qualitative descriptive analysis, the results show that the existence of open space in the present, such as in residential or residential groups, still exists. If in the past traditional settlements, the existence of open spaces was used as a means to gather and socialize, then in its current development, open space could be used as a means of playing and exercising for children, recreational activities (gathering on holidays), supported economic activities (traders who sell), as well as a means of worship (Eid al-Fitr / Eid al-Adha). This shows the development and diversity of functions and activities in the open space, so that its utilization can increase economic values, religious values and other social values.